THE EFFECT OF FIRM SIZE, LEVERAGE, AND PROFITABILITYTO FIRM STOCK RETURN (CASE STUDY OF BUILDING CONSTRUCTION SECTOR) - Justinadia, Diella
Since 2014, when Mr. Joko Widodo was appointed as President of Indonesia, infrastructure development continues to be shown as President Jokowi's main plan in increasing development in Indonesia. As a result, construction companies in Indonesia have clearly benefited from the Government's plan. Investors certainly want a positive return on funds invested in the company. So to attract investors, a company must be able to increase stock returns as reflected in an increase in the price of its shares and/or dividends distributed by the company.Factors affecting the stock return of the company include the size of the company, leverage, and profitability.